Real-world evidence on the efficacy of bivalent booster doses of SARS-CoV-2 vaccine in respect of monovalent boosters or primary cycle of vaccination: a narrative review - Sane Schepisi, Monica (Epidemiologia e prevenzione, 2023)
the objective of this review is to give an overall view of the knowledge on COVID-19 bivalent vaccines and to explore the available real-world evidence on their effectiveness in the Omicron era. Currently, bivalent vaccines are generally offered to all groups eligible for their next booster, as defined by the national vaccination campaigns, with varying policies between countries.The use of bivalent vaccines is supported by immunogenity studies, but these have produced contradictory conclusions and are not generally designed to measure clinical impact. in order to critically evaluate the available research on real-world efficacy, a systematic literature search was performed; three different web engines were used, including early-stage search platforms: PubMed, medRxiv and the Global research on coronavirus disease (COVID-19) database. no restrictions were imposed on language, setting or publication date. The research was last updated on 20 March 2023. the following outcomes were considered: infection, hospitalisation due to COVID-19 disease, admission to the emergency/urgency department, death. The following were considered as additional outcomes: variant-specific vaccine effectiveness; vaccine effectiveness waning over time. out of 876 references reviewed, 14 studies were finally included and extracted. The results of this review show modest to moderate additional protection from vaccination with bivalent BA.4-5 or BA.1 vaccines mRNA-booster against COVID-19-associated disease - Relative VE% ranging from 8 (95% CI 0-16) to 58.7 (95% 54.6-62.5)- and hospitalisation - Relative VE% ranging from 32.2 (2.5-60.1) to 80.5 (95% CI 69.5-91.5)-, when compared with a booster with a monovalent vaccine or with having completed only the primary course, during a period when BA.5 and other Omicron sublineage viruses predominated globally. the additional benefit of bivalent booster vaccines - compared to one or two monovalent booster vaccinations or compared to the primary course alone - in the prevention of SARS-CoV-2 Omicron infection appears to be small, especially in persons with previous Omicron infection, whereas modest to moderate protection from vaccination with bivalent BA.4-5 or BA.1 mRNA-booster vaccines as a fourth dose against COVID-19-associated illness and hospitalisation has been reported.